Impact of prior cancer history on the overall survival of patients newly diagnosed with cancer: A pan‐cancer analysis of the SEER database. Issue 7 (7th May 2018) - Zhou, Huaqiang; Huang, Yan; Qiu, Zeting; Zhao, Hongyun; Fang, Wenfeng; Yang, Yunpeng; Zhao, Yuanyuan; Hou, Xue; Ma, Yuxiang; Hong, Shaodong; Zhou, Ting; Zhang, Yaxiong; et al.
Abstract : The population of cancer survivors with prior cancer is rapidly growing. Whether a prior cancer diagnosis interferes with outcome is unknown. We conducted a pan‐cancer analysis to determine the impact of prior cancer history for patients newly diagnosed with cancer. We identified 20 types of primary solid tumors between 2004 and 2008 in the Surveillance, Epidemiology, and End Results database. Demographic and clinicopathologic variables were compared by χ 2 test and t ‐test as appropriate. The propensity score‐adjusted Kaplan‐Meier method and Cox proportional hazards models were used to evaluate the impact of prior cancer on overall survival (OS). Among 1, 557, 663 eligible patients, 261, 474 (16.79%) had a history of prior cancer. More than 65% of prior cancers were diagnosed within 5 years. We classified 20 cancer sites into two groups (PCI and PCS) according to the different impacts of prior cancer on OS. PCI patients with a prior cancer history, which involved the colon and rectum, bone and soft tissues, melanoma, breast, cervix uteri, corpus and uterus, prostate, urinary bladder, kidney and renal pelvis, eye and orbits, thyroid, had inferior OS. The PCS patients (nasopharynx, esophagus, stomach, liver, gallbladder, pancreas, lung, ovary and brain) with a prior cancer history showed similar OS to that of patients without prior cancer. Our pan‐cancer study presents the landscape for the survival impact of prior cancer across 20 cancer types. Compared to the patients without prior cancer, the PCI group had inferior OS, while the PCS group had similar OS. Further studies are still needed. Abstract : What's new? Prior cancer history often excludes patients from cancer clinical trials. However, whether a prior cancer diagnosis actually interferes with study outcomes is still unknown. In this study, the authors analyzed 20 different cancer types. These cancers fell into two categories: "prior cancer inferior" (PCI), in which patients had lower survival rates than those without prior cancer; and "prior cancer similar" (PCS), in which survival rates were similar. Almost half of the cancer types were PCS. These results suggest that not all prior cancers must be excluded from clinical trials.